Dissociative electron attachment to HGaF4 Lewis–Brønsted superacid. Issue 33 (14th August 2018) - Czapla, Marcin; Simons, Jack; Skurski, Piotr
Abstract : An excess electron attachment to the HGaF4 superacid induces its spontaneous fragmentation leading to H atom and GaF4 − superhalogen anion. Abstract : The consequences of an excess electron attachment to HGaF4 (HF/GaF3 ) superacid are investigated on the basis of theoretical calculations employing ab initio methods. It is found that the dipole potential of HGaF4 plays an important role in the initial formation of a dipole-bound anionic state. Due to the kinetic instability of that initially formed anion, a fragmentation reaction occurs promptly and leads to (GaF4 ) − and H as the final products. The energy profile of this process, its rate, and mechanism are presented and discussed.